LOSING BY LESS? IMPORT COMPETITION, UNEMPLOYMENT INSURANCE GENEROSITY, AND CRIME. (10th January 2019) - Beach, Brian; Lopresti, John
Abstract : Increased import competition from China has brought about a host of negative consequences for the most exposed industries and labor markets. Do social programs attenuate these harmful effects? We examine changes in import competition between 1990 and 2007, taking crime as our outcome of interest and unemployment insurance as our mitigating program. We find strong evidence that counties with access to more generous unemployment insurance experienced relatively smaller increases in trade‐induced property crime. This highlights a new and important positive externality of unemployment insurance. ( JEL H00, R10)